Using genomic data to unravel the root of the placental mammal phylogeny - Murphy, William J.; Pringle, Thomas H.; Crider, Tess A.; Springer, Mark S.; Miller, Webb (Genome Research, 2007)
The phylogeny of placental mammals is a critical framework for choosing future genome sequencing targets and for resolving the ancestral mammalian genome at the nucleotide level. Despite considerable recent progress defining superordinal relationships, several branches remain poorly resolved, including the root of the placental tree. Here we analyzed the genome sequence assemblies of human, armadillo, elephant, and opossum to identify informative coding indels that would serve as rare genomic changes to infer early events in placental mammal phylogeny. We also expanded our species sampling by including sequence data from >30 ongoing genome projects, followed by PCR and sequencing validation of each indel in additional taxa. Our data provide support for a sister-group relationship between Afrotheria and Xenarthra (the Atlantogenata hypothesis), which is in turn the sister-taxon to Boreoeutheria. We failed to recover any indels in support of a basal position for Xenarthra (Epitheria), which is suggested by morphology and a recent retroposon analysis, or a hypothesis with Afrotheria basal (Exafricoplacentalia), which is favored by phylogenetic analysis of large nuclear gene data sets. In addition, we identified two retroposon insertions that also support Atlantogenata and none for the alternative hypotheses. A revised molecular timescale based on these phylogenetic inferences suggests Afrotheria and Xenarthra diverged from other placental mammals ∼103 (95–114) million years ago. We discuss the impacts of this topology on earlier phylogenetic reconstructions and repeat-based inferences of phylogeny.
10.1101/gr.5918807